PENERAPAN PENDEKATAN KOOPERATIF DENGAN DUKUNGAN MODEL MATEMATIKA DALAM MATERI SPLTV DI SMA - Ferianti, Flesia Welly; Halini, Halini; Ahmad BS, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aimed to know the effectiveness of the application of a cooperative approach with the support of mathematical models in the material linear equation system of three variable in class X SMAS Santun Pontianak. The method used in this research is an experimental research method and the research design was pre-experimental design. There were four aspects that were in this research, such as the teacher’s class management, student activities, completeness of learning outcomes, and student responses. There were two techniques for collecting data, that’s are measurement techniques and observation techniques. Tools was used in this research were test results of the study, teacher’s class management observation sheet, student activity observation sheets, and response questionnaires. From the results of data analysis, the teacher’s class management in good category, student learning activities in active category, the completeness results of the study is not fulfilled classically, and student responses to learning in excellent category. So, learning using a cooperative approach with the support of an ineffective mathematical model was applied in the material linear equation system of three variable in class X SMAS Santun Untan Pontianak. Keywords:   Effectiveness, Cooperative Approach, Linear Equation System Of Three Variable